Stabilizing milk-derived extracellular vesicles (mEVs) through lyophilization: a novel trehalose and tryptophan formulation for maintaining structure and Bioactivity during long-term storage - Alan B. Dogan; Spencer R. Marsh; Rachel J. Tschetter; Claire E. Beard; Md R. Amin; L. Jane Jourdan; Robert G. Gourdie (Journal of Biological Engineering)
Abstract Extracellular vesicles (EVs) are widely investigated for their implications in cell-cell signaling, immune modulation, disease pathogenesis, cancer, regenerative medicine, and as a potential drug delivery vector. However, maintaining integrity and bioactivity of EVs between Good Manufacturing Practice separation/filtration and end-user application remains a consistent bottleneck towards commercialization. Milk-derived extracellular vesicles (mEVs), separated from bovine milk, could provide a relatively low-cost, scalable platform for large-scale mEV production; however, the reliance on cold supply chain for storage remains a logistical and financial burden for biologics that are unstable at room temperature. Herein, we aim to characterize and engineer a freeze-dried, mEV formulation that can be stored at room temperature without sacrificing structure/bioactivity and can be reconstituted before delivery. In addition to undertaking established mEV assays of structure and function on our preparations, we introduce a novel, efficient, high throughput assay of mEV bioactivity based on Electric Cell Substrate Impedance Sensing (ECIS) in Human dermal fibroblast monolayers. By adding appropriate excipients, such as trehalose and tryptophan, we describe a protective formulation that preserves mEV bioactivity during long-term, room temperature storage. Our identification of the efficacy of tryptophan as a novel additive to mEV lyophilization solutions could represent a significant advancement in stabilizing small extracellular vesicles outside of cold storage conditions.